PERAN KARAKTERISTIK SISTEM AKUNTANSI MANAJEMEN SEBAGAI VARIABEL YANG MEMEDIASI PENGARUH TEKNOLOGI INFORMASI DAN SALING KETERGANTUNGAN TERHADAP KINERJA MANAJERIAL (Studi Pada PD BPR BKK se-Jawa Tengah) - Wahyu Meiranto; Kiki Widiastuti; Elen Puspitasari (Dinamika Akuntansi Keuangan dan Perbankan, 2013)
One of the important role of Management Accounting Information System (MAS) is to provide information to the right people, the right way at the right time to improve management capabilities in understanding the circumstances around it, so it was able to identify the relevant activities appropriately. The purpose of this study is to empirically examine the role of MAS as variables that mediate the effect of information technology and interdependence on performance managerial of employees inthe local government enterprises are rural banks and financial institutions sub-Central Java (PD BPR BKK). The samples in this study were obtained according to the purposive sampling technique based on criteria derived from population consisting of employees or the manager at PD BPR BKK contained in Central Java. Data were analyzed using Partial Least Square (PLS) in a of Structural Equation Modeling (SEM). Role of characteristics of MAS as variable which mediate the effect of information technology and interdependence on managerial performance examined using Sobel Test. The results of this study indicate that information technology has an indirect positive effect and significant impact on managerial performance through MAS. Interdependence also has an indirect positive effect and significant impact on managerial performance through MAS. It can be concluded that the MAS has a role as a mediating influence between the variables information technology and interdependence on managerial performance.Keywords: management accounting information system, information technology, interdependence, mediating, managerial performance.